Attachment style moderates the relationship between social media use and user mental health and wellbeing. Issue 6 (June 2020) - Young, Lindsay; Kolubinski, Daniel C.; Frings, Daniel
Abstract: Background: Past research has correlated social media use with a variety of mental health outcomes – both positive and negative. The current study aims to explore two possible moderators of the link between social media use and mental health outcomes; specifically, the effects of having an anxious and/or avoidant attachment style. Method: A cross-sectional correlational design was implemented. Participants ( n = 124). aged ≥18 years completed scales measuring experiences in close relationships, general problematic Internet use, psychological wellbeing and satisfaction with life. Results: Negative relationships between problematic social media use and both psychological wellbeing and life satisfaction were observed. For psychological wellbeing, the relationship was strongest amongst individuals who were low in avoidant attachment and high in anxious attachment. Discussion: These results suggest that attachment style impacts the extent that social media affects user mental health and wellbeing; partly explaining paradoxical results in previous research. Conclusion: We suggest that individuals who are high in anxious attachment and low in attachment avoidance may be more susceptible to negative outcomes arising from problematic SNS use. Abstract : Psychology; Attachment; Social networks; Depression; Anxiety; Social Media